2009
DOI: 10.1111/j.1365-2249.2009.04054.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-transglutaminase antibodies in non-coeliac children suffering from infectious diseases

Abstract: SummaryAnti-transglutaminase antibodies are the diagnostic markers of coeliac disease. A role is suggested for infectious agents in the production of antitransglutaminase antibodies. The aim was to measure positive antitransglutaminase antibody levels in children with infectious diseases and to compare immunological and biological characteristics of the antitransglutaminase antibodies derived from these children with that from coeliac patients. Two hundred and twenty-two children suffering from infectious dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 21 publications
(24 reference statements)
1
36
0
3
Order By: Relevance
“…The introduction of endomysium antibodies was initially promising, because their sensitivity and specificity seemed to be at least 90-95%; but over time, issues regarding inter-observer reliance/interpretability and cost, have limited its use as the first-line screening tool for CD. Though TTG antibodies can also be elevated in non-CD diseases such as liver disease, 26 gastrointestinal infections 27 and certain heart diseases; 28,29 TTG, like EMA, offers high sensitivity and specificity. 30 One further test recently gained some popularity: This is for deamidated gliadin peptide antibodies (DGP); however, one meta-analysis found that TTG performs better than DGP.…”
Section: Prevalence Of Cd: ''That the Disease Is Common And Well Defimentioning
confidence: 99%
“…The introduction of endomysium antibodies was initially promising, because their sensitivity and specificity seemed to be at least 90-95%; but over time, issues regarding inter-observer reliance/interpretability and cost, have limited its use as the first-line screening tool for CD. Though TTG antibodies can also be elevated in non-CD diseases such as liver disease, 26 gastrointestinal infections 27 and certain heart diseases; 28,29 TTG, like EMA, offers high sensitivity and specificity. 30 One further test recently gained some popularity: This is for deamidated gliadin peptide antibodies (DGP); however, one meta-analysis found that TTG performs better than DGP.…”
Section: Prevalence Of Cd: ''That the Disease Is Common And Well Defimentioning
confidence: 99%
“…The CD-specific autoantibodies targeted against TG2 cause disorganization of the actin cytoskeleton [36]. Purified TG2 induced actin rearrangements and cell-cycle progression [37]. The disappearance of IgA antimicrofilament after gluten withdrawal predicted the normalization of intestinal mucosa and could be considered a useful tool in the follow-up of severe CD [38].…”
Section: Serological Testsmentioning
confidence: 99%
“…The AEA was determined using human umbilical cord sections as previously reported. 4 Serum IgA anti-TG, and organ-specific auto-antibodies (thyroperoxidase antibodies, glutamic acid decarboxylase autoantibodies, islet-antigen 2 antibodies) were all measured following the manufacturer's instructions (Eurospital, Trieste, Italy). Serum auto-antibodies were evaluated in our 2 cases and in patients highly suspected for celiac disease at diagnosis and on 3 more occasions during follow-up.…”
Section: Biopsy and Serum Analysismentioning
confidence: 99%
“…3 Anti-TG were identified during infections in 4% of infected children, whether they were celiac disease-related HLA carriers or not, and later disappeared on a normal diet. 4 We report 2 children with upper airway infection found to have a high serum concentration of anti-TG that did not originate in the intestine and were not related to gluten ingestion. Both were tested to measure the most common serum glutendependent organ-specific antibodies found in some patients with untreated celiac disease.…”
mentioning
confidence: 96%